2003
DOI: 10.3141/1854-04
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal Market Segmentation Approach to Mode Choice and Ridership Forecasting: Structural Equation Modeling

Abstract: The San Francisco Bay Area Water Transit Authority is evaluating expanded ferry service, as required by the California Legislature. As part of this process, Cambridge Systematics developed forecasts using a combination of market research strategies and the addition of nontraditional variables into the mode choice modeling process. The focus of this work was on expanding the mode choice model to recognize travelers' attitudes and different market segments. Structural equation modeling was used to simultaneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 11 publications
0
46
0
1
Order By: Relevance
“…Similarly, studies have examined the impact of environmental consciousness or protection tendency (based on diverse indicators collected from attitudinal surveys), revealing that environmental consciousness positively affects the probability of choice of active transport (walking and cycling), and reduces the probability of choosing private motorized vehicles (for example, see Outwater et al, 2003;Anable, 2005;Hunecke et al, 2007;Shiftan et al, 2008;Atasoy et al, 2010;Daly et al, 2011;Rieser-Schlusser and Axhausen, 2012; 1 While it is true that the power of the ICLV models arises in part through the use of a small set of latent variables to generate a parsimonious factor-analytic error dependency structure across a large number of alternatives in a choice model, and across these alternatives with other continuous/ordinal outcomes, the point is that almost all earlier studies have placed very restrictive factor-analytic structures by specifying a single latent variable (due to computational problems otherwise) rather than attempting to test (and capture) a richer factor analytic structure by specifying more latent variables. Tyrinopoulos and Antoniou, 2012;Hess et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies have examined the impact of environmental consciousness or protection tendency (based on diverse indicators collected from attitudinal surveys), revealing that environmental consciousness positively affects the probability of choice of active transport (walking and cycling), and reduces the probability of choosing private motorized vehicles (for example, see Outwater et al, 2003;Anable, 2005;Hunecke et al, 2007;Shiftan et al, 2008;Atasoy et al, 2010;Daly et al, 2011;Rieser-Schlusser and Axhausen, 2012; 1 While it is true that the power of the ICLV models arises in part through the use of a small set of latent variables to generate a parsimonious factor-analytic error dependency structure across a large number of alternatives in a choice model, and across these alternatives with other continuous/ordinal outcomes, the point is that almost all earlier studies have placed very restrictive factor-analytic structures by specifying a single latent variable (due to computational problems otherwise) rather than attempting to test (and capture) a richer factor analytic structure by specifying more latent variables. Tyrinopoulos and Antoniou, 2012;Hess et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In their work aiming to develop an attitudinal market segmentation approach to mode choice and ridership forecasting, Outwater et al [37] concluded that "individuals more aware of environmental issues are more motivated to use public transport, while on the contrary travelers more sensitive to stress tend to prefer car over public transport for non-work trips".…”
Section: Market Segmentation and User Oriented Approachesmentioning
confidence: 99%
“…Previous work in the area of marine operation and services tackled issues of planning for services (Cedar 2006), evaluation of services (Odek and Barthen 2009), forecasting demand (Laube and Dyer 2007;Outwater et al 2003), best practices for public outreach (Camay et al 2008), marine network design (Wang and Lo 2008), and intermodal modeling (East and Armstrong 1999). Ceder (2006) presented a planning approach with an evaluation procedure for making the best use of existing water and pier resources to improve public ferry transit through the provision of commercially-viable services in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Laube and Dyer (2007) presented a model for demand forecasting of the ferry service system to serve the National Park of New York Harbor. Outwater et al (2003) tackled the expansion of mode choice models to account for traveler attitudes and different market segments. The causal relationships between traveler socio-economic profile and travel attitudes towards ferry services of San Fransisco Bay Area were integrated into the mode choice models.…”
Section: Introductionmentioning
confidence: 99%